MITOS DALAM CERITA RAKYAT NUSANTARA ASUHAN MURTI BUNANTA: SEMIOTIKA ROLAND BARTHES - Puspitasari , Istianah; Ratnasari , Andaru (Universitas Hamzanwadi, 2025)
This research is motivated by the fact that myths have a historical foundation in society in the form of speech as a message, not only verbally, but also in the form of writing or images that have meaningful signs, one of which is the myth that is poured into children's literature. Children's literature tells past stories, whether in the form of legends, fairy tales, and folk tales and is closely related to myths that are still relevant to the present. The research aims to describe and explain the myths contained in the folklore of Murti Bunanta using Roland Barthes' thoughts, namely: (1) Myth as Stolen Language, (2) Myth as De-Politicized Speech, and (3) Inevitability and Limits of Mythology. This research method uses a qualitative descriptive method. Folklore of Murti Bunanta: Si Molek, Putri Mandalika, Ni Terong Kuning, Suwidak Loro, Topitu, and Senggutru as data sources. The results of the study Myth as Stolen Language and presenting events that connect the driving of the reasons or motives of the characters, Myth as De-Politicized Speech presents the driving of the character's actions towards the characters who play a role and are clearly strong and dominant. Inevitability and Limits Mythology is more dominant in showing events carried out by characters in unreasonable things. Myths are interpreted as uncertain meanings or other purposes, continuing to develop to convey messages.